Internasionalisasi Usaha Mikro, Kecil, Dan Menengah (Umkm) Ditinjau Dari Tipe Kepemilikan: Studi Empiris Di Jawa Timur - Herlina Yoka Roida; N. Agus Sunarjanto; William Jayaprana (Universitas Airlangga, 2010)
In the internationalization process, scales do not become an obstacle among small medium SMEs. However, the capacity to get market access is the most important consideration based the type of SMEs ownership. This reach draws the impact of ownership types to invoice internationalization. The model analysis used in this research are: (1) model 1 used to determine whether or not SMEs to export, and (2) model 2 used to determine the intensity of SMEs in exports that control by innovation (R&D expenditure), employment (SIZE) and sector choices. As a result, there is no significant impact of ownership type to the internationalization strategy. The decision mostly influenced by control variable which is sector choices, respectively.